2007
DOI: 10.1097/qai.0b013e3181568e3f
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Than-Expected Rates of Lactic Acidosis Among Highly Active Antiretroviral Therapy-Treated Women in Botswana

Abstract: Rates of lactic acidosis appear to be higher in southern Africa when compared with rates previously described elsewhere. Risk factors for the development of moderate to severe symptomatic hyperlactatemia or lactic acidosis appear to be multifactorial but include female gender and having a BMI of greater than 25. Additional studies are ongoing to evaluate for other possible risk factors, such as host genetic differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
67
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 21 publications
10
67
5
Order By: Relevance
“…A 2007 study found a similar percentage of lipodystrophy (34.2z) among Rwandan population of 409 adults (25) while Botswana study reported only 16z (26). A study in India, Kumarasamy et al reported a 42z incidence of skin rashes, which was much higher than that in our study (18.8z).…”
Section: Discussioncontrasting
confidence: 55%
“…A 2007 study found a similar percentage of lipodystrophy (34.2z) among Rwandan population of 409 adults (25) while Botswana study reported only 16z (26). A study in India, Kumarasamy et al reported a 42z incidence of skin rashes, which was much higher than that in our study (18.8z).…”
Section: Discussioncontrasting
confidence: 55%
“…Hence it is conceivable from this study that there is no association between CD4 count and SHL/ LA among the SA population, in good agreement with the reports of Osler and others. [11,27] However, our findings contradict the results obtained by some researchers, in which a strong association between patient age [25] and CD4 count [24,26] and SHL/LA was observed. Several POLG1 mutations have been studied, resulting in deletions or point mutations in mtDNA and decreased polymerase activity.…”
Section: Researchcontrasting
confidence: 57%
“…These risk factors are consistent with those reported by other studies in related settings, [10,12,14] as well as in other studies globally. [8,15,[24][25][26] In this study, the baseline age of the cases and controls was significantly different (p=0.015), with a median age of 38 (IQR 33 -45) and 33 (IQR 28 -40) years for cases and controls, respectively. This is in good agreement with studies that have shown associations between SHL/ LA and advanced age.…”
Section: Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…Lactic acidosis, a rare but life-threatening mitochondrial toxicity associated with long-term NRTI use, occurs approximately 20-fold more frequently in women (31,41), suggesting possible sex-based differences in NRTI cellular pharmacology. Current data regarding associations between the cellular pharmacology of these drugs and sex are variable and inconclusive.…”
mentioning
confidence: 99%